Microaggressions: Prevalence and Perspectives of Residents and Fellows in Post-Graduate Medical Education in Kuwait - Al Rashed, Asmaa; Al Yousef, Rawan; Alhouti, Farah (Frontiers in Surgery, 2022)
Objective: Microaggressions prevalence in post-graduate medical education is unknown in Kuwait. The objective is to determine the prevalence and to capture the perspectives of microaggression among post-graduate trainees in Kuwait. Materials and Methods: Cross-sectional study. Anonymous online survey targeting residents and fellow in Kuwait. Data collected included demographics, level of training, country of training, microaggression experience, types, and response. Univariate and multivariate analysis were performed using Chi-square test and binary logistic regression, respectively. Results: 319 participants (69.1% females) included 52% junior residents, 39.2% senior residents and 8.78% fellows. Forty-three percent were aware of microaggressions definition. The percentage was significantly higher in respondents from Gulf/Middle East Countries (57.9%) than from Kuwait. Approximately three-quarters experienced microaggressions. Senior residents were more likely to report exposure to microaggressions (OR = 2.4, P < 0.05) and had higher odds of exposure than juniors (OR = 9.85, P < 0.05). Exposure to microaggressions was highest in surgery/surgical specialties. The most common act of microaggression was verbal, followed by invalidation/dismissal of thoughts/ideas, and then acts of discrimination. Of those who experienced microaggressions, two-thirds thought that the experience had a psychological effect on them. Both groups reported low confidence in dealing with microaggressions (Gulf/Middle East Countries 18.8% and Kuwait 30.1%), the difference was not statistically significant. Conclusions: Microaggressions are common among post-graduate medical trainees in Kuwait. Implementation of strategies to manage it is necessary. Further research on its impact on medical-training outcome is needed.